Reward contingency modulates neuronal activity in rat septal nuclei during elemental and configural association tasks - Nozomu eMatsuyama; Nozomu eMatsuyama; Teruko eUwano; Etsuro eHori; Taketoshi eOno; Hisao eNishijo (Frontiers in Behavioral Neuroscience, 2011)
It has been suggested that septal nuclei are important in the control of behavior during various reward and non-reward situations. In the present study, neuronal activity was recorded from rat septal nuclei during discrimination of conditioned sensory stimuli (CSs) of the medial forebrain bundle associated with or without a reward (sucrose solution or intracranial self-stimulation, ICSS). Rats were trained to lick a spout protruding close to the mouth just after a CS to obtain a reward stimulus. The CSs included both elemental and configural stimuli. In the configural condition, the reward contingency of the stimuli presented together was opposite to that of each elemental stimulus presented alone, although the same sensory stimuli were involved. Of the 72 responsive septal neurons, 18 responded selectively to the CSs predicting reward (CS+-related), four to the CSs predicting nonreward (CS0-related), nine to some CSs predicting reward or nonreward, and 15 nondifferentially to all CSs. The remaining 26 neurons responded mainly during the ingestion/ICSS phase. A multivariate analysis of the septal neuronal responses to elemental and configural stimuli indicated that septal neurons encoded the CSs based on reward contingency, regardless of the stimulus physical properties and were categorized into three groups; CSs predicting the sucrose solution, CSs predicting a nonreward, and CSs predicting ICSS. The results suggest that septal nuclei are deeply involved in discriminating the reward contingency of environmental stimuli to manifest appropriate behaviors in response to changing stimuli.